Experience with gluteal V‐Y fasciocutaneous advancement flaps in vulvar reconstruction after oncological resection and a modification to the marking: Playing with tension lines. Issue 1 (10th October 2018) - Fin, Alessandra; Rampino Cordaro, Emanuele; Guarneri, Gianni F.; Revesz, Susanna; Vanin, Michele; Parodi, Pier C.
Abstract : Many post‐vulvectomy vulvar reconstruction solutions, using local fasciocutaneous flaps where possible, have been proposed. We report the use of V‐Y advancement flaps from the gluteal fold in medium to large vulvar reconstructions and a simple modification we made to the technique in order to minimise wound‐related complications. Between 2006 and 2016, 30 vulvar reconstructions were performed via a total of 59 flaps, 24 of which were raised using the proposed modification to the plasty design. Short‐ and long‐term (24 months) follow‐up data were analysed, postoperative flap sensitivity was tested, and any arising complications were recorded. The mean age of patients treated was 75.3 years (51‐92 years). The mean monolateral defect dimensions were 7.5 × 4.7 × 2.8 cm. Minor complications were recorded in 23% of patients (14% of flaps). One case of ostial stenosis occurred. Micturition and ambulation recovery was rapid, and flap sensitivity was fully restored 24 months after reconstruction. Scars were well hidden by natural soft tissue folds. The outcomes in this case series confirm that the gluteal V‐Y advancement fasciocutaneous flap is a useful and simple technique for reconstructing even large vulvar defects. It has a low functional and aesthetic impact and enables rapid return to autonomy. Moreover, the simple modification to the V‐Y flap proposed, designed to reduce tension at the apical part of the wound, appears to reduce the complication rate.